PENERAPAN PRINSIP GOOD CORPORATE GOVERNANCE DALAM PENGELOLAN DANA DESA DI DESA BANTEA BUTON TENGAH - Oki Syahnakir; La Utu; Wahyuni Rahmah (STIE ENAM ENAM KENDARI, 2022)
The purpose of this study was to determine the application of good corporate governance principles in managing village funds in Bantea Village, Gu District, Central Buton Regency in 2021. The research method used was qualitative with descriptive qualitative research. The research was conducted because the Village Fund has a big influence on village development and the Village Fund is also prone to abuse. Therefore, it is necessary to apply the principles of good corporate governance. The results of this study indicate that the Bantea Buton Tengah Village Government has implemented the principles of good corporate governance, namely transparency and accountability in planning, implementation and accountability. However, the low quality of the available resources in Bantea Village has delayed the realization of the Bantea Village Fund Budget.